2014
DOI: 10.1186/s40662-014-0003-1
|View full text |Cite
|
Sign up to set email alerts
|

Small incision lenticule extraction (SMILE) history, fundamentals of a new refractive surgery technique and clinical outcomes

Abstract: This review summarizes the current status of the small incision lenticule extraction (SMILE) procedure. Following the early work by Sekundo et al. and Shah et al., SMILE has become increasingly popular. The accuracy of the creation of the lenticule with the VisuMax femtosecond laser (Carl Zeiss Meditec) has been verified using very high-frequency (VHF) digital ultrasound and optical coherence tomography (OCT). Visual and refractive outcomes have been shown to be similar to those achieved with laser in situ ker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
90
0
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(103 citation statements)
references
References 84 publications
1
90
0
12
Order By: Relevance
“…This central removal of material also alters the biomechanical characteristics of the cornea, potentially affecting among other things the applanatory measurement of internal ocular pressure in the course of investigation of glaucoma (22)(23)(24). Kerato-refractive procedures are not discussed in more detail here owing to the limited scope of this article, but the relevant literature is cited in review articles (25,26).…”
Section: Myopiamentioning
confidence: 99%
“…This central removal of material also alters the biomechanical characteristics of the cornea, potentially affecting among other things the applanatory measurement of internal ocular pressure in the course of investigation of glaucoma (22)(23)(24). Kerato-refractive procedures are not discussed in more detail here owing to the limited scope of this article, but the relevant literature is cited in review articles (25,26).…”
Section: Myopiamentioning
confidence: 99%
“…after treatment than after LASIK, lower decrease and faster recovery of corneal sensation than after LASIK, less theoretical reduction in the biomechanical strength of the cornea, and better wound-healing response than after LASIK. 5,6,12 The hypothesis of this study was that corneas with lower deformation may offer greater resistance to separation of the lenticule from the residual stroma during the surgery assuming that these corneas are biomechanically stiffer.…”
Section: Discussionmentioning
confidence: 99%
“…Although the 2013 study by Trost et al 4 showed that 6.5-mm diameter corneal flaps could be created in rabbits with no unintended UV-induced damage to the cornea at a total radiant exposure of 6.9 J∕cm 2 , it did not establish an operational range and safety margin for 355-nm lasers. A measurement of the actual damage thresholds is important to establish the safety limits of 355-nm lasers for the full range of flap cutting parameters as well as other potential applications, such as refractive lenticule extraction, 6 lamellar keratoplasty, 7 or cataract surgery. 8 Of the three major damage mechanisms for any laser ocular surgery, photomechanical, photothermal, and photochemical, we are mostly concerned with photochemical damage for 355-nm lasers as it sets a hard limit on the total energy that can be delivered during a procedure.…”
Section: Safety Of Cornea and Iris In Ocular Surgery With 355-nm Lasementioning
confidence: 99%